Developing a courseware database for the AudioGraph : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science at Massey University - Pan, Jun (Massey University, 2000)
The goal of this project is to investigate and prototype a database driven server for the editing and delivery of multimedia courseware. This project required the analysis, design, and construction of a client/server based, distributed educational system. The components of the project are a relational database server with a particular database schema that can be downloaded or distributed with an existing project and the AudioGraph. The AudioGraph is an application using a multi-media tool to publish university lectures, tutorials or training material on the Web. The front-end interface is a Java application that lets the lecturers or students interact with the database. This system can be used to keep track of various stages of courseware development and web publishing. The overall aim was a flexible and adaptive system with the current lecture development and environment maintained. The system may be distributed on Windows NT, Unix and Macintosh platforms and so is portable and extendible and is platform-independent. The background and technology employed in the project is introduced. Each stage of the project process is explained in terms of the development lifecycle of the system. A limitation imposed by multi-platform compatibility is discussed and the achievement is presented by screenshots. Through the report, the structure of the file, run time environment, inter-process communication, user interface, and server access are explained.
Keywords: Computer-assisted instruction; Programming; Client/server computing; Database design; Distance education